2013
DOI: 10.7860/jcdr/2013/5140.2751
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Insensate Neuropathy- Is Height a Risk Factor?

Abstract: Introduction: Peripheral insensate neuropathy is one of the most commonest and the earliest forms of peripheral neuropathy. It is one of the leading causes of the disability in working population who are at risk. Methods:A study was conducted in Kasturba medical college (Manipal university) in the year 2009-12, which included examination of 818 people of more than 30yrs of age by random sampling method who were attending the outpatient clinic. A monofilament was used to determine the peripheral insensate neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 25 publications
(23 reference statements)
5
29
0
Order By: Relevance
“…This finding is supported by another analysis in which the TTE model was expanded to include eight MMAE‐containing ADCs . It was reported that height, which is highly correlated with body weight, is an important and independent risk factor for PN . There is also a trend for higher risk with increasing serum albumin concentrations.…”
Section: Discussionmentioning
confidence: 58%
“…This finding is supported by another analysis in which the TTE model was expanded to include eight MMAE‐containing ADCs . It was reported that height, which is highly correlated with body weight, is an important and independent risk factor for PN . There is also a trend for higher risk with increasing serum albumin concentrations.…”
Section: Discussionmentioning
confidence: 58%
“…One possible reason for the lower rates of neuropathy among South Asians could be their shorter average height than Caucasians. Height was found to be significantly correlated with peripheral insensate neuropathy in people with and without diabetes in a study in Manipal, South India . A similar effect of height on peripheral neuropathy was reported in people with T2DM in Sri Lanka .…”
Section: Diabetic Neuropathymentioning
confidence: 59%
“…In addition, the estimated effect of BWT was not influenced by inclusion of diabetes as a covariate in the model. Hence, taken together, our analysis suggests that the increased risk associated with a high BWT may be related to the length and surface area of the axonal nerve fibers being available for the ADC exposure rather than obesity‐induced inflammation or diabetes. It is also possible that a combination of these effects is in play.…”
Section: Discussionmentioning
confidence: 82%